UPAYA PEMANGGILAN PAKSA OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) TERHADAP PELAKU USAHA YANG TIDAK HADIR DALAM PENYELESAIAN SENGKETA KONSUMEN - Mantili, Rai (VYAVAHARA DUTA, 2018)
One of the authorities of the Consumer Dispute Settlement Agency (BPSK) is to receive both written and unwritten complaints from consumers regarding the occurrence of violations of consumer protection. Article 52 Sub-Article g of the Consumer Protection Law (UUPK) au- thorizes BPSK to summon business actors who allegedly violate consumer protection. However, in practice in the field, BPSK is not authorized to force involuntary calling of business actors so that many business actors refuse to be present at consumer dispute resolution in BPSK. This research is Normative and Analytical Descriptive Research. In this case, it is a Nor- mative Legal Research in the form of research to find the Law of Concreto, the research to find the law for a case in concreto is an attempt to find out whether the appropriate law to apply in cocreto in order to solve a particular case and see the rule of law is found . This research will illustrate various legal issues and other symptoms related to cases concerning consumer protec- tion and BPSK Implementation of consumer protection law enforcement in practice is not yet fully fea- sible. It can be seen apart from awareness of the ability and independence of consumers to protect themselves against the rights and kewajibanya, also can be seen from law enforcement officers who have not performed optimally. efforts that can be made by BPSK after forced calling of business actors who refuse to attend the consumer dispute resolution can make a verdict verdict if the business actor is not present 3 times on the summons of the session by BPSK as stipulated in Article 52 UUPK and Kemendag. 35/2001.